2008
DOI: 10.1080/00103620801925901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Broiler Litter Management Practices on Phosphorus, Copper, Zinc, Manganese, and Arsenic Concentrations in Maryland Coastal Plain Soils

Abstract: The objective of this research was to assess the long-term effects of broiler litter applications on soil phosphorus (P), copper (Cu), zinc (Zn), manganese (Mn), and arsenic (As) concentrations in Chesapeake Bay watershed Coastal Plain soils. Litter and soil samples were collected from 10 farms with more than 40 years of broiler production and from wooded sites adjacent to fields and were analyzed for P and metal contents. Averaged over farms, total P and metal concentrations in the litter were 12.8 g kg 21 P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 23 publications
4
13
0
Order By: Relevance
“…Mean levels of total C, total N, NH 4 + –N, M3‐Na, M3‐Fe, M3‐Zn, WE‐Na, WE‐Fe, and WE‐Zn did not differ significantly between L+ and L– soil samples. Results were consistent with earlier reports of soil P accumulation from repeated litter applications (Kingery et al, 1994; Moore and Edwards, 2007; Codling et al, 2008) and supported the hypothesis that a high P level could indicate a history of litter applications and its corollary that a low P level was an indication that litter had not been applied.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Mean levels of total C, total N, NH 4 + –N, M3‐Na, M3‐Fe, M3‐Zn, WE‐Na, WE‐Fe, and WE‐Zn did not differ significantly between L+ and L– soil samples. Results were consistent with earlier reports of soil P accumulation from repeated litter applications (Kingery et al, 1994; Moore and Edwards, 2007; Codling et al, 2008) and supported the hypothesis that a high P level could indicate a history of litter applications and its corollary that a low P level was an indication that litter had not been applied.…”
Section: Resultssupporting
confidence: 91%
“…In paired comparisons (L+ and L–), pH was higher for L+ for 19 of 20 soil pairs, and the mean difference (L+ minus L–) was 0.66 units. Increased pH has also been reported for similar paired soil comparisons in earlier studies from Alabama (Kingery et al, 1994), Oklahoma (Sharpley et al, 1993), and Maryland (Codling et al, 2008). Higher soil pH due to litter application has also been reported from controlled litter treatment studies in North Carolina (Crane et al, 1980) and Georgia (Gascho and Hubbard, 2006).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…In addition to its effect on crop yield, different authors (Kingery et al, 1994;Whittington, 2007;Codling, 2008) suggested that the application of organic materials based on the N requirements of crops has unfavorable effects on soil fertility and the environment due to the accumulation of soil phosphorus and metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…We had hypothesized that addition of FGDG would reduce As in runoff, similar to what has been observed for P after coapplication of FGDG with BL (Moore and Miller, 1994; Watts and Torbert, 2009; Endale et al, 2014; Torbert and Watts, 2014; Watts and Torbert, 2016). This was not observed, possibly because phosphate in BL can cause displacement of arsenate from adsorbents in surface soil, promoting runoff or leaching of arsenate from BL (Adeli et al, 2007; Codling et al, 2008; Chaney, 2012). Although arsenical use in broiler feed has stopped due to regulatory change and BL should no longer add appreciable As to soils, legacy levels of As in soils may still pose a threat to surface and ground waters.…”
Section: Resultsmentioning
confidence: 95%